State Power and the Role of International Organizations: A Comparative Analysis of Realism and Liberalism - Santiago Eca Fernandes, Agustinus (Cita konsultindo, 2025)
The discourse of international relations has long been characterized by debates on the dominant role of the state and the significance of international organizations within the global system. This article aims to provide a comparative analysis of realism and liberalism in their perspectives on state power and the role of international organizations. The study employs a literature review method with a qualitative comparative approach, drawing upon both classical and contemporary works in international relations theory. The findings indicate that realism positions the state as the primary actor, emphasizing the anarchic nature of the international system, national interests, and the distribution of power, while international organizations are perceived merely as instruments of powerful states. Conversely, liberalism highlights the importance of interdependence, international institutions, as well as norms and international law as mechanisms to reduce conflict and promote cooperation. This analysis demonstrates that both perspectives remain relevant in understanding the dynamics of contemporary global politics, though each has its limitations in explaining the complexity of international interactions. The study contributes theoretically to the development of international relations scholarship and offers practical implications for the formulation of foreign policy and multilateral diplomacy strategies.